Synthesis of mesoporous film (polyaniline-manganese dioxide) from lyotropic liquid crystalline template - Chai, Raymond Goh Ming (2010)
Mesoporous polyaniline (PANI)-manganese dioxide (MnO2) films have been successfully fabricated from hexagonal structured lyotropic liquid crystalline phase with Brij 56 surfactant. The phase structures of the lyotropic liquid crystalline templates are characterized by polarized optical microscopy (POM) and low-angle X-ray diffraction (XRD). The synthesized mesoporous films are probed with scanning electron microscopy (SEM), wide-angle XRD and low-angle XRD for surface structures. The mesoporous PANI-MnO2 composite films heat annealed at 200°C were characterized using cyclic voltammetry (CV) and choronopotentiometry (CP) in 0.5 M Na2SO4 electrolyte for supercapacitor applications. In addition, the probed films show excellent capacitive behavior within potential window of -0.1 to 0.7 V, a specific capacitance of 265 F/g is attained at the scan rate of 100 mV s-1. A maximum average specific capacitance of 543 F/g is obtained when the mesoporous composite film is characterized using CP with charge density of 5 mA/cm2. These results signifies that mesoporous PANI-MnO2 films electrodeposited from lyotropic liquid crystalline phases exhibits promising electrochemical behaviors.